اسلام میں میڈیا اور ابلاغ کے اخلاقی اصول؛ ایک تجزیاتی مطالعہ: Islamic Ethical Frameworks for Media and Communication: An Analytical Exploration - Dr. Muhammad Usman Khalid,; Hafiza Kiran Saba,; Amna Ahmad, (Al-Amīr Research Journal for Islamic Studies, 2025)
The importance of media and communication in contemporary times is undeniable. It serves as a means of information dissemination and influences public opinion on social, political and religious matters. Islam, being a comprehensive way of life, provides clear ethical principles for media based on truthfulness, justice and trustworthiness. Truthfulness is a core value in Islamic teachings. The Quran emphasizes avoiding falsehood and presenting accurate information. Misinformation can harm individuals and society alike. Similarly, justice and fairness are integral principles. Media should maintain impartiality while presenting news or opinions, ensuring fairness even when it concerns opposing views. Trustworthiness is another critical principle. Media professionals are entrusted with conveying reliable and complete information. Prophet Muhammad (PBUH) highlighted the importance of trust, indicating that sharing information requires honesty and integrity. Furthermore, Islam advises avoiding fitna (discord and chaos), as it leads to societal unrest. Media should promote harmony and refrain from spreading content that incites conflicts or divisions. Respect for privacy and dignity is vital. Islam emphasizes protecting the honor and confidentiality of individuals, discouraging intrusion into private lives. Additionally, media should focus on promoting positive and constructive content. The Quran advises speaking good and beneficial words that enhance moral values and contribute to societal reform. In conclusion, Islam's ethical guidelines for media emphasize truth, justice, trust, privacy and constructive communication. Adherence to these principles ensures that media fulfills its responsibilities effectively while fostering societal well-being. These guidelines are especially relevant today, given the growing influence of media in shaping public narratives and societal norms. Keywords: Media, Ethics, Privacy, Social Reform, Islam, honesty, justice, trustworthiness, Islamic teachings, communication theory.